Formulation and evaluation of soap preparations from Curcuma zedoaria rhizome - Yuliawati, Yuliawati; maimum, Maimum; Iskandar, Mirna Marhami; Sani, Fathnur (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Maintaining skin cleanliness is one of the effective ways to maintain the health of the body caused by infections caused by microorganisms. A simple way to maintain skin cleanliness is to clean the skin using soap. Soap functions to clean dirt and can inhibit pathogens found on the surface of the epidermis. The purpose of this study is to determine the effect of different concentrations of white temu rhizome infusion on solid soap preparations Method: this study is experimental. The difference in the concentration of active ingredients in the infusion of white rhizomes was 0%, 5%, 7.5%, and 10%. The process of making infusions starts from making simplicia powder. The preparation tests carried out are organoleptic testing, pH test, foam height test and foam stability. Results: the results of the study showed that the amount of simplicia powder obtained was 535.1 grams with a percentage of simplicia yield of 17.40%. The results of the characteristic evaluation were obtained in the organoleptic test of the color of the difference influenced by the difference in the concentration of the added infusion. The results of the pH test of the solid soap formula of the white temu rhizome infusion meet the set standards, namely with a pH value between 9.27 – 9.87 so that it is safe to use on the skin. Conclusion: Based on the research conducted, it can be concluded that the infusion of rhizome of Curcuma zedoaria can be formulated into preparations in the form of solid soap and the difference in the concentration of infusion of curcuma has an influence on organoleptic testing, pH, and foam height as well as foam stability.